Microproject – ’Teaching identities and alphabets’: Preliminary results on multiple literacies from the arts in teachers’ initial training in Language Teaching - Francos Maldonado, Concepción (Huarte de San Juan. Filología y Didáctica de la Lengua, 2022)
This article summarises the general lines of a microproject, Teaching identities and alphabets, which forms part of a teaching innovation project in initial training Constructing an interdisciplinary and intercultural approach through art in the initial training of teachers and pedagogues, made up of other microprojects, one of which is common to the subject Design of materials for education and training in the degree in Pedagogy. Among the objectives of the general innovation project are: to develop an interdisciplinary and intercultural methodology through the arts, favouring multi-literacy, favouring collaboration with the educational area of Museums, as a factor of innovation in the initial training of future teaching professionals. The project helps teachers in initial training to take into consideration the relevance of the teaching of Language Didactics and the role of multi-literacy. It facilitates communication with the arts and their symbols, the significance of interdisciplinarity, broadens the viewpoint and creativity. It also contributes to a critical exercise on the teaching identity and to turn experience into shared knowledge.